Education Financing Management in Improving the Quality of School Education - Baraz Yoechva Alfaiz; Sutriani; Ruslan; Nur Anim Jauhariyah (ICO EDUSHA, 2024)
This study aims to describe and analyze several aspects of the implementation of financing management, namely: (a) transparency, (b) accountability, (c) effectiveness, and (d) efficiency in improving academic quality at Babussalam Blimbingsari Junior High School. This research was conducted with a qualitative approach, using interview, observation, and documentation methods as data collection techniques. The validity of the data was tested through source triangulation. The results of the study show that the implementation of financing management at Babussalam Blimbingsari Junior High School to support the improvement of education quality is carried out based on the principles of transparency, accountability, effectiveness, and efficiency. These principles are realized through providing access to information related to school financial management, involvement of related parties in decision-making, open budget reporting, forming a financial management team, and implementing education quality improvement programs. This success is supported by competent human resources, good coordination skills, budgeting according to needs, and proper program planning. The management of education financing management at Babussalam Blimbingsari Junior High School is carried out in a structured and professional manner. The use of the right budget is a key factor in the success of the educational process in schools. In addition, the analysis of education quality showed that there was a positive relationship between financing management and improving the quality of education. Financing management has proven to be able to answer the needs of programs and policies that support quality improvement at Babussalam Blimbingsari Junior High School. Keywords: Management, Education Financing, Education Quality